2018
DOI: 10.1371/journal.pone.0207069
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of sensory neuronal subtypes innervating mouse tongue

Abstract: The tongue is uniquely exposed to water-soluble environmental chemicals that may lead to injury or tumorigenesis. However, comparatively little research has focused on the molecular and functional organization of trigeminal ganglia (TG) afferent neurons innervating the tongue. The current study identified and characterized lingual sensory neurons based on a neuronal subtype classification previously characterized in the dorsal root ganglion (DRG) neurons. We employed immunohistochemistry on transgenic reporter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 77 publications
4
48
0
Order By: Relevance
“…Recently, Prato et al ., demonstrated that mechanically-insensitive C-Fibers that express the marker CHRNA3 are converted to mechanosensitive neurons in the presence of NGF 38 . Interestingly, CHRNA3 is expressed in lingual neurons 39 and the majority of MIA fibers detected in our study were C-fibers (Table 1 ). Moreover, NGF is shown to be overexpressed and released by OSCC tumor contributing to oral cancer pain 12 .…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Recently, Prato et al ., demonstrated that mechanically-insensitive C-Fibers that express the marker CHRNA3 are converted to mechanosensitive neurons in the presence of NGF 38 . Interestingly, CHRNA3 is expressed in lingual neurons 39 and the majority of MIA fibers detected in our study were C-fibers (Table 1 ). Moreover, NGF is shown to be overexpressed and released by OSCC tumor contributing to oral cancer pain 12 .…”
Section: Discussionmentioning
confidence: 67%
“…In addition to the findings described above, use of tongue-nerve electrophysiology revealed three interesting observations about trigeminal afferent responses. First, C-LTMR fibers were identified in lingual sensory neurons, despite the presence of very low proportion of tyrosine hydroxylase or VGLUT3 expression (both being markers of C-LTMR in dorsal root ganglion (DRG) neurons as reported recently 39 41 . This reflects and emphasizes the differences between DRG neurons and trigeminal ganglia (TG) neurons.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…If the measure was normally distributed, then differences were determined using a one-way analysis of variance with a Tukey's post hoc analysis. If they were not normally distributed differences across multiple groups were compared using a Kruskal-Wallis test, while two groups were compared using a (Wu, Arris et al 2018). Therefore, we used TrkB CreER :alkaline phosphatase (AP) mice to reconstruct single taste nerve axons innervating the tongue (Rutlin, Ho et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Polymodal nociceptors respond to acidification as well as other potentially painful stimuli 42 (Bessou and Perl 1969). Many small caliber polymodal nociceptors that innervate the oral cavity 43 (Kichko, Neuhuber et al 2018, Wu, Arris et al 2018) express one or both of the pH-sensitive 44 transient receptor potential (Trp) channels, TrpA1 (Wang, Chang et al 2011) and TrpV1 45 (Tominaga, Caterina et al 1998). TrpA1 has been implicated especially in responsiveness to 46 weak acids capable of penetrating cell membranes to produce intracellular acidification (Wang,47 Chang et al 2011).…”
Section: Introduction 22mentioning
confidence: 99%